Respuesta :
So the first step when dealing with circle problems is to put the equation in standard form.
x² + y² + 6y = 7
Original Problem.
(x+0)² + (y² + 6y) = 7
Expanded x variable and put y values in parentheses.
(x+0)² + (y² + 6y + 9) = 7 + 9
Added 9 to both sides.
(x+0)² + (y+3)² = 16
Factored out y variables.
(x+0)² + (y+3)² = 4²
Standard form.
Now to find the center, just look inside the parentheses. Inside the x set there is the x value, inside the y set there is the y value. (x+0) and (y+3). The center is (0,3). That eliminates answer choices B) and D). Now the radius is the square root of the last number in the standard equation. 4². The square root of 4 squared is 4. Therefore the radius is 4. That eliminates answer C).
That leaves us with one answer: A) center (0,3) and radius 4.
Hope that helps!
Answer:
Option B) center [tex](0,-3)[/tex] and radius [tex]4[/tex]
Step-by-step explanation:
we know that
The equation of the circle into center radius form is equal to
[tex](x-h)^{2}+(y-k)^{2}=r^{2}[/tex]
where
(h,k) is the center of the circle
r is the radius of the circle
In this problem we have
[tex]x^{2} +y^{2}+6y=7[/tex]
so
convert to center radius form
Complete the square. Remember to balance the equation by adding the same constants to each side
[tex]x^{2} +(y^{2}+6y+9)=7+9[/tex]
[tex]x^{2} +(y^{2}+6y+9)=16[/tex]
Rewrite as perfect squares
[tex]x^{2} +(y+3)^{2}=16[/tex]
[tex]x^{2} +(y+3)^{2}=4^{2}[/tex]
The center is the point [tex](0,-3)[/tex]
The radius is [tex]4[/tex] units